Nanographenes as Active Components of Single-Molecule Electronics and How a Scanning Tunneling Microscope Puts Them To Work - Müllen, Klaus; Rabe, Jürgen P (Accounts of chemical research, 2008)
Single-molecule electronics, that is, realizing novel electronic functionalities from single (or very few) molecules, holds promise for application in various technologies, including signal processing and sensing. Nanographenes, which are extended polycyclic aromatic hydrocarbons (PAHs), are highly attractive subjects for studies of single-molecule electronics because the electronic properties of their flat conjugated systems can be varied dramatically through synthetic modification of their sizes and topologies. Single nanographenes provide high tunneling currents when adsorbed flat onto conducting substrates, such as graphite. Because of their chemical inertness, nanographenes interact only weakly with these substrates, thereby preventing the need for special epitaxial structure matching. Instead, self-assembly at the interface between a conducting solid, such as the basal plane of graphite, and a nanographene solution generally leads to highly ordered monolayers. Scanning tunneling spectroscopy (STS) allows the current−voltage characteristics to be measured through a single molecule positioned between two electrodes; the key to the success of STS is the ability to position the scanning tunneling microscopy (STM) tip freely with respect to the molecule in all dimensions, that is, both parallel and perpendicular to the surface. In this Account, we report the properties of nanographenes having sizes ranging from 0.7 to 3.1 nm and exhibiting various symmetry, periphery, and substitution types. The size of the aromatic system and the nature of its perimeter are two essential features affecting its HOMO–LUMO gap and charge carrier mobility in the condensed phase. Moreover, the extended π area of larger substituted PAHs improves the degree of self-ordering, another key requirement for high-performance electronic devices. Self-assembly at the interface between an organic solution and the basal plane of graphite allows deposition of single molecules within the well-defined environment of a molecular monolayer. We have used STM and STS to investigate both the structures and electronic properties of these single molecules in situ. Indeed, we have observed key electronic functions, rectification and current control through single molecules, within a prototypical chemical field-effect transistor at ambient temperature. The combination of nanographenes and STM/STS, with the PAHs self-assembled in oriented molecular mono- or bilayers at the interface between an organic solution and the basal plane of graphite and contacted by the STM tip, is a simple, reliable, and versatile system for developing the fundamental concepts of molecular electronics. Our future targets include fast reversible molecular switches and complex molecular electronic devices coupled together from several single-molecule systems.